Analisis Pengaruh Economic Value Added, Profitabilitas dan Market Value Added Terhadap Harga Saham Perusahaan - Risal Rinofah; Pristin Prima Sari; Heni Nur Amrina (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The purpose of this study is to find out whether the effect of Market Value Added, Profitability, and Market Value Added on stock price. Sampling in this study is a purposive sampling method. Then the data is tested using multiple regression analysis. The results of the t test showed that the Economic Value Added has a signification value of 0,018 which means smaller than 0,05 and the calculated value of -2.441<t tablel 2.00758 then H1 is accepted. Profitability has a signification value of 0,034 greater than 0,05 and a calculated value of 2.182>t table 2.00758 then H2 is accepted, Market Value Added has significant value of 0,223 greater than 0,05 and the value of t calculated -1.235<t table 2.00758 then H3 is rejected. The results of the F test showed that Economic Value Added, Profitability, Market Value Added have a calculated F value of 2,933 and sig. 0,042. Because the value F calculated 2.933>F table 2.773 and sig. value 0,042<0,05. It can be concluded that partially Economic Value Added has a significant negative effect on stock price, Profitability has a significant effect on stock price, Market Value Added has no significant effect on stock price and simultaneously Economic Value Added, Profitability, Market Value Added has a significant effect on stock price Keywords: Economic Value Added, Profitabilitas, Market Value Added, Stock Price